2015
DOI: 10.1051/epjconf/201510200011
|View full text |Cite
|
Sign up to set email alerts
|

Heating and cooling processes in disks

Abstract: Abstract. This chapter summarises current theoretical concepts and methods to determine the gas temperature structure in protoplanetary disks by balancing all relevant heating and cooling rates. The processes considered are non-LTE line heating/cooling based on the escape probability method, photo-ionisation heating and recombination cooling, free-free heating/cooling, dust thermal accommodation and high-energy heating processes such as X-ray and cosmic ray heating, dust photoelectric and PAH heating, a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…For the quiescence data, the emission is close to being optically thin in the weak line for both the Fe I 6256/6191 Å and the Fe I 6462/6393 Å pairs. This is significantly different from what has been observed in EX Lupi (Sicilia-Aguilar et al 2012, 2015 and DR Tau (Beristain et al 1998), where narrow lines are optically thicker than the broad components and can be traced back to dense, hot spots on the stellar surface 8 , and suggests a disk origin.…”
Section: Line Ratio Constraints On the Inner Diskcontrasting
confidence: 96%
See 1 more Smart Citation
“…For the quiescence data, the emission is close to being optically thin in the weak line for both the Fe I 6256/6191 Å and the Fe I 6462/6393 Å pairs. This is significantly different from what has been observed in EX Lupi (Sicilia-Aguilar et al 2012, 2015 and DR Tau (Beristain et al 1998), where narrow lines are optically thicker than the broad components and can be traced back to dense, hot spots on the stellar surface 8 , and suggests a disk origin.…”
Section: Line Ratio Constraints On the Inner Diskcontrasting
confidence: 96%
“…The emission lines were visually selected and classified using the NIST database (Ralchenko et al 2010;Kramida et al 2018) and the list of lines observed in Z CMa and other outbursting objects (van den Ancker et al 2004;Sicilia-Aguilar et al 2012, 2015. The narrow neutral metallic emission lines in quiescence 1 http://www.astrouw.edu.pl/asas/explanations.html reveal a radial velocity ∼27 ± 3 km s −1 , which is consistent with previous estimates (∼30 km s −1 ; Hartmann et al 1989).…”
Section: Emission Line Classificationmentioning
confidence: 99%
“…PAH heating and grain radiative cooling), chemical processes (e.g. exothermic reactions), hydrodynamic work/viscous heating and cosmic rays (a review is given by Woitke 2015). Many of these heating/cooling terms are linked to the composition of the gas, requiring chemical and thermal calculations to be solved iteratively.…”
Section: Reactionmentioning
confidence: 99%
“…As heating effectively occurs throughout the spectrum, cooling of dust is, on the other hand, temperature dependent. Therefore, due to the ice bands in especially the near-IR (NIR) and the far-IR (FIR), the dust grain is either cooled or heated more depending on its temperature (see for a review Woitke 2015).…”
Section: Icy Grainsmentioning
confidence: 99%